Evaluation of thermal climatic region areas in terms of building density in urban management and planning for Burdur, Turkey - Cetin, Mehmet; Adiguzel, Fatih; Gungor, Senay; Kaya, Efdal; Sancar, Mustafa Cihat (Springer Science and Business Media LLC, 2019)
The main aim of this research is to investigate the bioclimatic conditions of Burdur city center in different terrain areas by taking measurements at 20 different points in the same time zone over the city. In order to investigate the bioclimatic comfort properties of Burdur City by taking into consideration the number of floors in Burdur city center, on 17 February 2018 between 16.00 and 16.30 h, temperature and relative humidity measurements were made with two Benetech GM8910 devices from 20 different locations with different characteristics. In addition to the parameters taken from 20 points, the physiological equivalent temperature (PET) index which includes the human energy balance was used. Thermal detection values of 20 stations were calculated. Multiple linear regression models were used for spatial distribution of the obtained values. According to the analysis, urban high building density areas have higher PET values in most of the day than in other terrestrial areas. Between these areas and open areas was a difference of 0.4–1.2 °C, between parks 2.2–3 °C, between locations 1.4–2.2 °C, and between rural areas 1.7–2.5 °C per day. There are mean PET differences.
Keywords: China; Turkey; GIS (geographic information system); Tilia Tomentosa | Electrometallurgy | Arcview; Thermal climate; Urban policy; Climate conditions; Burdur [Turkey]; Urban planning; Burdur; Building; Spatial distribution; Measurements; Temperature; Urban area; GIS; Comfort; Index; Regions; Urban management and plan; Time-series; Environmental Sciences; 11. Sustainability; 13. Climate action